Neogene evolution and demise of the Amapá carbonate platform, Amazon continental margin, Brazil. (July 2019) - Cruz, A.M.; Reis, A.T.; Suc, J.P.; Silva, C.G.; Praeg, D.; Granjeon, D.; Rabineau, M.; Popescu, S.M.; Gorini, C.
Abstract: The Amazon continental shelf hosted one of the world's largest mixed carbonate-siliciclastic platforms from the late Paleocene onwards - the Amapá carbonates. The platform architecture, however, remains poorly understood and causes and timing of the cessation of carbonate deposition are still controversial. Here we present a stratigraphic analysis of the Neogene succession of the Amapá carbonates, based on a grid of 2D/3D seismic data correlated to revised micropaleontological data from exploration wells. The results provide improved constraints on the age of the transition from predominantly carbonate to siliciclastic sedimentation, which is shown to have varied through time across three different sectors of the shelf (NW, Central and SE). Four Neogene evolutionary stages of carbonate deposition could be defined and dated with reference to the new age model: (1) between ca. 24 and 8 Ma a predominantly aggrading mixed carbonate-siliciclastic shelf prevailed across the entire region carbonate production gave way to siliciclastic sedimentation across the Central and SE shelves; (2) between 8 and 5.5 Ma carbonate production continued to dominate the NW shelf, as deposition was able to keep up with base level oscillations; (3) between 5.5 and 3.7 Ma (early Pliocene), sediment supply from the paleo-Amazon River promoted the progressive burial of carbonates on the inner NW shelf, while carbonates production continued on the outer shelf (until 3.7 Ma). Longer-lasting carbonate sedimentation on the NW shelf can be explained by a lesser influx of siliciclastic sediments due to the paleo-geography of the Central shelf, characterized by a 150-km-wide embayment, which directed most terrigenous sediments sourced from the paleo-Amazon River to the continental slope and deep ocean; (4) from 3.7 Ma onwards, when the Central shelf embayment became completely filled, continuous sediment supply to the NW shelf resulted in the final transition from carbonate to siliciclastic-dominated environments on the entire Offshore Amazon Basin. Highlights: New age models allow to clarify the Neogene history of the Amazon shelfal carbonates. Differential subsidence strongly controls shelf architecture between ca. 24–3, 7Ma Higher siliciclastic influx suppressed the Central and NW shelf carbonates at ca. 8Ma Carbonate production locally persisted on the NW Amazon shelf until ca. 3.7Ma Reduction of regional subsidence rates led to the death of shelfal carbonates.